P140 A need to reinforce the importance of pregnancy testing and correct antibiotic regimen: a re-audit of pid management against bashh guidelines. (8th June 2017) - Burridge, Joanna; Aziz, Najia; Mani, Reena
Abstract : Introduction: BASHH guidelines (2011) for the management of pelvic inflammatory disease (PID) recommend one of two antibiotic regimens for outpatient treatment. In addition, patients should be offered a pregnancy test and full screening for sexually transmitted infections (STI). Aim(s)/objectives: To review PID management across the sexual health clinics, comparing it to the previous year's audit and BASHH guidelines. Methods: Data was retrospectively collected from December 2015 until March 2016. Data collected included whether pregnancy was excluded, STI screening, antibiotic regimen used, provision of written information, partner notification, and outcome at any follow up. Results: 51 patients were identified, 2 were excluded due to treatment by their GP. 100% of cases had at least one sign or symptom suggestive of PID. 47/49 (96%) of cases had STI screening; 41/49 (84%) had a HIV screen as part of this. Pregnancy was excluded in 22/49 (45%) of cases. A BASHH recommended antibiotic regimen was used in 28/49 (57%) of cases. Of the 21 of non-compliant cases, only 4/21 had a documented allergy or intolerance that precluded standard treatment. Discussion: Since the last audit, recommended antibiotic treatment for PID has improved, but remains low at 57%. Pregnancy exclusion was low at 45%, compared with 70% at the last audit. Differences in how healthcare professionals record information on the electronic system could partially account for this. Actions have been taken to improve treatment and pregnancy testing by giving individual feedback to the clinicians, with a re-audit planned to assess the outcome of these interventions.